2016
DOI: 10.4238/gmr.15027745
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic influences of colchicine on phenological and molecular diversity of Calendula officinalis L.

Abstract: ABSTRACT. Six different colchicine concentrations: 0, 400, 800, 1200, 1600, and 2000 ppm, in combination with four soaking time treatments (1, 2, 3, and 4 h), were selected to assess the effects on germination, vegetative growth, and flower yield components in calendula plants. The molecular diversity among the treatments was assessed using ten SRAP marker combinations. Seed soaking in colchicine significantly enhanced both the fresh and the dry shoot and root masses, flowering date, number of flowers per plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Colchicine is an important mutagen that works by preventing the microtubules formation and doubles the number of chromosomes. It is commonly used to develop polyploid plants and functions as a mitotic poison by producing many mutagenic effects on plants [28]. As microtubules function in chromosome segregation, colchicine induces polyploidy by preventing the segregation of chromosomes during meiosis that results into half of the gametes (sex cells) containing double the chromosome number than usual.…”
Section: Induction Of Polyploidymentioning
confidence: 99%
See 1 more Smart Citation
“…Colchicine is an important mutagen that works by preventing the microtubules formation and doubles the number of chromosomes. It is commonly used to develop polyploid plants and functions as a mitotic poison by producing many mutagenic effects on plants [28]. As microtubules function in chromosome segregation, colchicine induces polyploidy by preventing the segregation of chromosomes during meiosis that results into half of the gametes (sex cells) containing double the chromosome number than usual.…”
Section: Induction Of Polyploidymentioning
confidence: 99%
“…This “gigas effect” is mostly observed in different plant organs of commercial interests such as leaves, seeds and flowers [79]. Doubling through colchicine caused an increase in number of leaves, number of branches, plant height and stem length in salvia ( Salvia coccinea cv Coral Nymph) [42], jasmine tobacco ( Nicotiana alata ) [43], selfheal ( Prunella vulgaris ) [48], lily ( Lilium ) [41], chaste tree ( Vitex agnus castus ) [12], orchid ( Dendrobium nobile ) [40], ornamental ginger [80], crape myrtle ( Lagerstroemia indica ) [62], calendula ( Calendula officinalis ) [28], matted sea-lavender ( Limonium bellidifolium ) [53], white orchid tree ( Bauhinia acuminate ) [55] and London plane ( Planatus acerifolius ) [71]. Induced polyploidy also increased the leaf color in balsam ( Impatiens balsamina ), [73], self-heal ( Prunella vulgaris ) [48], wishbone flower ( Torenia fournieri ) [46], marigold ( Tagates erecta ) [63], chaste tree ( Vitex agnus castus ) [12] and chrysanthemum ( Dendranthema grandiflora ) [78], along with increasing their leaf area as well.…”
Section: Induction Of Polyploidymentioning
confidence: 99%
“…While conducting research on jute (Corchorus olitorius L.), Nura et al (2011) [16] found stimulatory and inhibitory effects of lower and higher doses colchicine on plant growth parameters. El-Nashar and Ammar (2016) [10] also reported the similar results in Calendula officinalis L. [12] demonstrated that P deficiency led to reduction in leaf size and hence, decreased photosynthetic capacity leading to growth inhibition.…”
Section: Resultsmentioning
confidence: 63%
“…In addition, colchicine also has a similar effect as plant growth regulators. It is influenced by developmental variances, either stimulatory or inhibitory (El-Nashar & Ammar, 2016). A few investigations directly compare the impacts of colchicine (Tank & Thaker, 2014) and plant growth regulators on plant morphology (Abd El-Latif et al, 2018).…”
Section: Mv1 Generation Plantlet Charactersmentioning
confidence: 99%